Active symptom control with or without oral vinorelbine in patients with relapsed malignant pleural mesothelioma (VIM): A randomised, phase 2 trial. (June 2022) - Fennell, Dean A.; Porter, Catharine; Lester, Jason; Danson, Sarah; Taylor, Paul; Sheaff, Michael; Rudd, Robin M; Gaba, Aarti; Busacca, Sara; Nixon, Lisette; Gardner, Georgina; Darlison, Liz; et al.
Summary: Background: Currently, there is no US Food and Drug Administration approved therapy for patients with pleural mesothelioma who have relapsed following platinum-doublet based chemotherapy. Vinorelbine has demonstrated useful clinical activity in mesothelioma, however its efficacy has not been formally evaluated in a randomised setting. BRCA1 expression is required for vinorelbine induced apoptosis in preclinical models. Loss of expression may therefore correlate with vinorelbine resistance. Methods: In this randomised, phase 2 trial, patients were eligible if they met the following criteria: age ≥ 18 years, Eastern Cooperative Oncology Group (ECOG) performance status 0 or 1, histologically confirmed pleural mesothelioma, post platinum-based chemotherapy, and radiological evidence of disease progression. Consented patients were randomised 2:1 to either active symptom control with oral vinorelbine versus active symptom control (ASC) every 3 weeks until disease progression, unacceptable toxicity or withdrawal at an initial dose of 60 mg/m 2 increasing to 80 mg/m 2 post-cycle 1. Randomisation was stratified by histological subtype, white cell count, gender, ECOG performance status and best response during first-line therapy. The study was open label. The primary endpoint was progression-free survival (PFS), measured from randomisation to time of event (or censoring). Analyses were carried out according to intention-to-treat (ITT) principles. Recruitment and trial follow-up are complete. This trial is registered with ClinicalTrials.gov, number NCT02139904. Findings: Between June 1, 2016 and Oct 31, 2018, we performed a randomised phase 2 trial in 14 hospitals in the United Kingdom. 225 patients were screened for eligibility, of whom 154 were randomly assigned to receive either ASC + vinorelbine ( n = 98) or ASC ( n = 56). PFS was significantly longer for ASC+vinorelbine compared with ASC alone; 4.2 months (interquartile range (IQR) 2.2–8.0) versus 2.8 months (IQR 1.4–4.1) for ASC, giving an unadjusted hazard ratio (HR) of 0·60 (80% CI upper limit 0.7, one-sided unadjusted log rank test p = 0.002); adjusted HR 0.6 (80% CI upper limit 0.7, one-sided adjusted log rank test p < 0.001). BRCA1 did not predict resistance to ASC+vinorelbine. Neutropenia was the most common grades 3, 4 adverse events in the ASC +vinorelbine arm. Interpretation: Vinorelbine plus ASC confers clinical benefit to patients with relapsed pleural mesothelioma who have progressed following platinum-based doublet chemotherapy. Funding: This study was funded by Cancer Research UK (grant CRUK A15569).